Oral Health and Related Quality of Life in Older People: A Sys-tematic Review and Meta-Analysis - Saber Azami-Aghdash; Fatemeh Pournaghi-Azar; Ahmad Moosavi; Mohammad Mohseni; Naser Derakhshani; Riaz Alaei Kalajahi (Tehran University of Medical Sciences, 2021)
Background: Of the most important implications and complaints in the elderly group of the population, is oral and dental health problems. This study aimed to assess oral health- related quality of life in older people. Methods: To data collection, databases were searched including PubMed, EMBASE, Scopus, SID, MagIran, Cochrane Central Register of Controlled Trials and scholar google The keywords were "older adults", "Geriatric" Elderly", "Older", "Aged", "Ageing", "Oral health", "Oral hygiene" and "Quality of life", "QOL. For manual searching, several specialized journals of related scope as well as the finalized articles' reference list were searched. Studies from 1st Jan 2000 to 30th Jan 2017 were included. Studies were subjected to meta-analysis to calculate indexes, using CMA:2 (Comprehensive Meta-Analysis) software. Results: Totally, 3707 articles were searched that 48 of them were subjected to the oral and dental health-related quality of life in 59 groups of the elderly population with the mean age of 73.57+6.62 in the 26 countries. The obtained percentage values of dental and oral health were 80.2% (0-60), 14.8% (0-12), 16.4% (0-70), 22% (0-14 or 0-59) and 19.2% (0-196) for GOHAI with the additive method, GOHAI with Simple Count Method, OHIP-14 with the additive method, OHIP-14 with Simple Count method and OHIP-49 with additive method indexes, respectively. Conclusion: The elderly group of the population had no proper oral health-related quality of life. Regarding the importance and necessity of oral and dental health and its effect on general health care in the target group, it is recommended to improve dental hygiene in the mentioned group of population.